Marketing Mix Affect Choosing Services Behavior on Traditional Trade of Consumer in Ratchaburi province - Charoensawat, Piyaporn (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The objectives of this research were 1) to study the marketing mix affect choosing services behavior on Traditional Trade of consumer in Ratchaburi province 2) to compare choosing services behavior on Traditional Trade of consumer in Ratchaburi province distinguish by the general data. The sample sizes composed of 400 persons who the consumers enter to use the Traditional Trade services in Ratchaburi province. The instrument collected the data by questionnaires which had 0.934 confidence values by Cronbach Alpha coefficient and 1.00 Index of item objective congruence (IOC).The statistics analyzed the data such as percentage, mean, standard deviation, one-way analyses of variances, and multiple regression analysis by the level statistical significant at 0.05 was valuable specification. The result of the research found that The marketing mix about Traditional Trade in Ratchaburi province were the most important level (means 3.58) and found that the consumer behaviors were choosing services of the Tradition Trade in Ratchaburi province at the most level (means 3.81) also. As for the hypothesis testing found that the difference general data of the answer such as age and educational factors were different choosing services behavior of Traditional Trade of consumer in Ratchaburi province at 0.05 significant level and found that the marketing mix such as price, promotion, product, physical evidence and process were influence to choosing service behavior on Traditional Trade of consumer in Ratchaburi province at 0.05 significant level. Article history : Accepted 27 October 2015 SIMILARITY INDEX = 0.00